EFFECT OF IRRIGATION ON ONE-YEAR GROWTH OF MULBERRY SEEDLINGS USED IN HIGHWAY LANDSCAPING (American Journal of Interdisciplinary Research and Development, 2024)
It is known that the use of advanced agrotechnical measures based on the soil and climate conditions for the cultivation of tree-like plants in nurseries gives good results. During the cultivation of seedlings, the demand for water and nutrients is different in different phases of the plant. Due to this, in the course of our research, agrotechnical measures were applied to seedlings based on plant and soil requirements in the phases of growth and development.